Simultaneous Heart–Liver Transplantation for Congenital Heart Disease in the United States: Rapidly Increasing With Acceptable Outcomes. Issue 4 (13th April 2021) - Cotter, Thomas G.; Wang, Jennifer; Peeraphatdit, Thoetchai; Sandıkçı, Burhaneddin; Ayoub, Fares; Kim, Gene; Te, Helen; Jeevanandam, Valluvan; Sabato, Diego; Charlton, Michael
Abstract : Background and Aims: There are more adults than children living with congenital heart disease (CHD) in the United States, with a growing proportion requiring heart–liver transplantation (HLT). Our aim was to ascertain the frequency, outcomes, and prognostic factors in this patient population. Approach and Results: United Network for Organ Sharing data on adult patients who underwent heart transplantation (HT) from 2009 through March 2020 were analyzed. The primary study outcome was patient survival. Cox proportional‐hazards modeling assessed for mortality associations. There were 1, 084 HT recipients: 817 (75.4%) CHD HTs only, 74 (6.8%) CHD HLTs, 179 (16.5%) non‐CHD HLTs, and 14 (1.3%) heart–liver–kidney transplants. The number of CHD HLTs increased from a prior rate of 4/year to 21/year in 2019. Among patients with CHD, the 5‐year survival rates were 74.1% and 73.6% in HTs only and HLTs, respectively ( P = 0.865). There was a higher rate of allograft failure attributable to rejection in CHD HTs only compared with CHD HLTs (3.2% versus 0.4%; P = 0.014). Only 25 out of 115 HT‐performing hospitals undertook CHD HLTs. Higher‐volume centers (averaging one CHD HLT per year) had a 5‐year patient survival rate of 83.0% compared with 61.3% in lower‐volume centers ( P = 0.079). Among HLT recipients, total bilirubin (hazard ratio [HR], 1.06; 95% confidence interval [CI], 1.01‐1.12) and diabetes (HR = 2.97, 95% CI = 1.21‐7.31) were independently associated with increased mortality risk, whereas CHD and age were not. Conclusions: The rate of HLT for adult CHD in the United States is rising dramatically. The survival outcomes between CHD HT only and CHD HLT groups are comparable; however, the HLT group had lower rates of acute rejection. Among HLT recipients, diabetes and elevated bilirubin are associated with increased posttransplant mortality risk. An average of one CHD HLT per year could be considered a minimum quality metric at transplant centers.